Lapa da Bugalheira (Torres Novas): review of the remains recovered in the archaeological intervention carried out there in 1941: DOI: https://doi.org/10.5281/zenodo.10402473 - Cardoso, João Luís (2023)
A review of the archaeoloical artifacts collected in the first archaeological intervention in 1941 at the necropolis of Lapa da Bugalheira (Torres Novas) preserved at the Geological Museum (LNEG) is presented, completed by a set of the new radiocarbon dates, which attest to the use of the funerary space during the Early Neolithic, the Middle Neolithic, the Late Neolithic and Chalcolithic, confirmed by its typology.